1977
DOI: 10.1161/01.cir.56.1.106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of left ventricular load and contractility on mitral regurgitant orifice size and flow in the dog.

Abstract: Acute mitral regurgitation (MR) was produced in 12 dogs by closed chest partial valvulectomy and the relative contributions of MR pressure gradient (MRG), the time for regurgitant flow (VSI), and the MR orifice area (MRA) to mitral regurgitant volume (MRV) assessed. Aortic and left atrial pressures, biplane left ventricular (LV) angiography, forward flow and mitral regurgitant flow (MRF) were measured following MR induction and following augmentation of left ventricular end-diastolic volume (EDV), increased ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Although it was previously proposed that the size of the regurgitant orifice diminished in situations with increased ventricular contractility or reduced intraventricular volume 26,27 , or both, this theory could not explain our results, because the velocity of the jet and not the regurgitation volume was the factor determining the size of the regurgitant area in color flow mapping 28 . Based on this, the mechanism of the difference observed between digoxin and enalapril could be explained by the capacity of the former to reduce the systolic preejection period 29,30 .…”
Section: Discussioncontrasting
confidence: 62%
“…Although it was previously proposed that the size of the regurgitant orifice diminished in situations with increased ventricular contractility or reduced intraventricular volume 26,27 , or both, this theory could not explain our results, because the velocity of the jet and not the regurgitation volume was the factor determining the size of the regurgitant area in color flow mapping 28 . Based on this, the mechanism of the difference observed between digoxin and enalapril could be explained by the capacity of the former to reduce the systolic preejection period 29,30 .…”
Section: Discussioncontrasting
confidence: 62%
“…The size of the effective regurgitant orifice is dependent on annular dimensions, leaflet length, and the integrity of the papillary muscle apparatus. Acutely, augmentation of loading conditions leads to ventricular enlargement, mitral annular dilatation, and increased regurgitant flow (5,35). Although a similar process has been suggested chronically (16), it has never been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis associated with MR varies directly with the severity of the regurgitation and the effect of the incompetent valve on LV systolic function (6,9). In acute experimental MR, the regurgitant orifice varies with loading conditions, ventricular size, and annular dimensions, as well as within the cardiac cycle (5,15,34,35). However, it is unclear in chronic MR whether the regurgitant orifice is dynamic and can further influence ventricular remodeling.…”
mentioning
confidence: 99%
“…Several factors, including LV size, extent of emptying, mitral annular diameter, papillary muscle function, and left atrial size, have been implicated. 9,[25][26][27] Experimental and clinical studies have also shown that the severity of functional MR often varied over time as a result of dynamic changes in the mitral regurgitant orifice, changes in ventricular-atrial pressure gradients, or both. 24 -27 For instance, the severity of functional MR has been shown to increase during isometric exercise and to decrease during dobutamine and nitroglycerin infusion.…”
Section: Mechanisms Of Exercise-induced Mrmentioning
confidence: 99%